The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00415-009-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers in Guillain-Barré syndrome – Where do we stand?

Abstract: Guillain-Barré syndrome (GBS) is an acute inflammatory polyneuropathy affecting the myelin-protein sheathing and the axons themselves to various degrees. Damage to these structures causes biomarkers to be released into the adjacent body fluid compartment. In case of the proximal nerve roots these biomarkers diffuse into the cerebrospinal fluid (CSF). Here we review the literature on CSF biomarkers in GBS, including a discussion of CSF basic findings, myelin sheath-associated markers (myelin basic protein), axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 78 publications
(122 reference statements)
5
33
1
1
Order By: Relevance
“…Previous studies demonstrated oligosaccharide structures of GD3, GD1a, GM1 and LPS similar to GT1a in other stubs of C. jejuni isolated from GBS patients using similar methods [30]. The capability of C. jejuni LPS in producing antiganglioside IgM and IgG antibodies in rats refers to the immunological importance of this imitation [31]. The same results were obtained for mice and rabbits [32].…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies demonstrated oligosaccharide structures of GD3, GD1a, GM1 and LPS similar to GT1a in other stubs of C. jejuni isolated from GBS patients using similar methods [30]. The capability of C. jejuni LPS in producing antiganglioside IgM and IgG antibodies in rats refers to the immunological importance of this imitation [31]. The same results were obtained for mice and rabbits [32].…”
Section: Discussionsupporting
confidence: 67%
“…10 These distinct mechanisms are in line with current serologic testing, with anti-glycan antibodies more closely associated with non-AIDP subtypes of GBS. 1 As would be predicted, anti-GM1, GD1b, and GQ1b were not detected in our patient's serum.…”
Section: Go To Section 4 Sectionsupporting
confidence: 62%
“…Sharief et al (1993) did not observe upregulation in TNF-␣ levels in cerebrospinal fluid (CSF), but serum TNF-␣ levels were significantly elevated and concluded that TNF-␣ played important role in the pathogenesis of GBS [6]. While studying CSF biomarkers in GBS, Brettschneider et al (2009) reported significant increase of TNF receptor and TNF-␣ mRNA in GBS; however TNF-␣ protein was increased only in a few patients [35]. Sivieri et al (1997) did not find significant levels of TNF-␣ in serum as well as in CSF, and commented that cytokines could not be easily detected in the biologic fluids like CSF because of their short half-life [36].…”
Section: Discussionmentioning
confidence: 96%